Medical services at the first Winter Youth Olympic Games 2012 in Innsbruck/Austria - Blank, C.; Schamasch, P.; Engebretsen, L.; Haslinger, S.; Ruedl, G.; Fink, C.; Schobersberger, W. (British Journal of Sports Medicine, 2012)
Background The Youth Olympic Games (YOG) are a new format designed by the International Olympic Committee. So far no reference data are available regarding the organisation or implementation of the medical services that were needed for the Winter Youth Olympic Games that took place for the first time in Innsbruck 9-24 January 2012.Objectives (1) To provide insight into what is needed to prepare for such a complex high level sporting event from a medical perspective, (2) to provide data on medical services for future organising committees and (3) to provide information on different National Olympic Committee (NOC) delegation structures and the consequences of registering a National Olympic Committee Team Physician.Methods A medical information system in the form of a patient data-management system was developed with all involved parties to standardise data collection. All medical encounters occurring at any IYOGOC medical service centre (including physiotherapy and psychology facilities) were tracked and collected in daily reports. Data evaluation was prepared based on different interest groups (Athletes, National Olympic Committees, Workforce, International Olympic Committee and Media) and analysed.Results 327 medical encounters (42.8% athletes; out of these, 57.9% were accounted to athletes with own NOC team physician) were seen during the YOG 2012. The total number of hospital transports was 27.3%, of which 8.9% were hospitalised with an average length of 1.9 nights. Physiotherapy usage was low with only 19 medical encounters resulting in a referral to physiotherapy accounting for 67 treatments during the entire YOG. Psychological care service was not used at all. The main reason for illnesses was disorders of the respiratory system (28.8%), injuries mostly affected upper extremities (49.6%) and were mostly diagnosed with lacerations and contusions (26.2%). Injury (70.7%) and illness (29.3%) incidences in athletes were slightly lower than previous studies showed. 40.0% of NOC delegations registered their own team physicians, which led to a significant difference in usage frequency of medical service (-3%, p=0.012).Conclusions Medical service coverage at the first Winter Youth Olympic Games seemed to be appropriate. No disaster or epidemic disease challenged the medical service plan. Future organising committees could use the provided data as a reference for their planning efforts.